CONTENT ANALYSIS OF AL-QUR'AN SCIENCE INTEGRATION IN CHILDREN'S ANIMATED SERIAL OF RIKO THE SERIES ON HUJAN’S EPISODE - Dadan Suryana; Resti Yulia; Safrizal Safrizal (Ta'dib, 2021)
The Qur'an is a source of value in the development of religion, morals, and knowledge for early childhood, especially for Muslim children. The integration of science-based knowledge is often highlighted at every level of education, especially in PAUD. This study uses a qualitative descriptive with the type of document analysis or content analysis. The data analysis technique used refers to the Saussure model. The stages in the analysis of research data are content analysis, information grouping, data interpretation, and verification. Testing the validity of the data using the credibility test, namely by increasing the persistence of researchers in terms of reviewing the important points of the analyzed content. The results showed that the animated film Riko the series became a science learning solution that was integrated with Al-Qur'an learning to give meaning to Al-Qur'an learning so that it was not limited to memorization but could be directly related to children's daily lives.